Indolactam-V Is Involved in the CH/x Interaction with Pro-I I of the PKCδ C1B Domain: Application for the Structural Optimization of the PKCδ Ligand. - Nakagawa, Yu; Irie, Kazuhiro; Yanagita, Ryo C.; Ohigashi, Hajime; Tsuda, Ken-ichiro (Journal of the American Chemical Society, 2005)
The article presents information on protein kinase C (PKC) isozymes are the main receptors of tumor promoters such as phorbol esters and teleocidins. After hydrolysis of the acetal, the asymmetric Strecker reaction was applied to the resulting aldehyde to give an (R)-amino nitrile diastereoselectively. The nitrile group was converted to the methyl ester, which was then reduced with lithium borohydride. Reduction of the nitro group and removal of the phenylethanol group of 4 were achieved by hydrogenation.